The effect of mental and psychological disorder in criminal offences: a comparative study - Muhammad Husni, Ahmad; Muhammad Husni, Amin (Zes Rokman Resources, 2024)
This research discusses about the effect of psychological and mental disorder and their responsibility in the Islamic and Civil laws. The question that arouses is, do the people that have mental or psychological illness need to be responsible for the mistakes they did? The aim of this research is to explain the limit set by the laws towards the person that commits crime in the state of mental and psychological abnormalities. This research will compare the Islamic and crime laws in Malaysia to find the clear explanation for the mentioned problem. Hence, this research has been done to compare the effects of crime done by people that deals with mental and psychological disorder through the Islamic laws against the civil laws prescribed by the National legislation. The qualitative method is used to get the result of the research through data analysis. The qualitative method has been used to get the result through the data analysis. The finding tells that there is an exception in Fiqh method which explains if the people that commit crime have mental disorder, hence they are not capable to be charged for any crime done by them. The exception in Fiqh explains that one with brain abnormality will be exempted from any offence. Likewise, the Criminal Law in Malaysia also gives special exception towards the crime done by the mental and psychological patients.